HUBUNGAN ANTARA PENGETAHUAN, PRAKTIK PENERAPAN SOP, PRAKTIK PENGGUNAAN APD DAN KOMITMEN PEKERJA DENGAN RISIKO KECELAKAAN KERJA DI PT X TANGERANG - Farah Avianti Putri; Suroto Suroto; Ida Wahyuni (Jurnal Kesehatan Masyarakat (Undip), 2017)
Approximately 85-96%of work accident caused by malicious behavior or unsafe acts. Malicious behavior is human failure in following the requirements and work procedure, which has been set. The implementation of occupational safety and health has done well, but there are some workers who are not obey the rules and values of occupational safety and health. As seen some workers who do not use PPE during work. There are also works who do not comply the work SOP. This study aims to analysis correlation between knowledge, practice of implementing SOP, practice on using of PPE, and worker commitment with risk of work accidents in PT. X Tangerang. The research design used was analytical survey method with corss sectional approach. Population in this research is workers at PT. X Tangerang workshop with total 44 workers. The Sample in this study was taken from the total population. The research instrument in this study was a questionnaire with closed questions. Statistical analysis used was Rank Spearman Correlation test. The result showed no relationship between knowledge (p = 0,529) with risk of work accidents. While, there are 3 variable research showed there are correlation between practice of implementing SOP (p = 0,035), practice on using of PPE (p = 0,015), and worker commitment (p = 0,015) with risk of work accidents. Companies should pay attention to SOP placement, enforce rewards and punishment to workers, conducting daily morning safety talks, and involve workers in establishing or upgrading corporate health and safety values.